IMPLEMENTASI PERAN PUSAT PELAPORAN TERHADAP TRANSAKSI KEUANGAN (PPATK) DITINJAU DALAM UNDANG- UNDANG TINDAK PIDANA PENCUCIAN UANG - Dewantara Jaya (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2019)
This study aims to determine how the PPATK's Role in preventing and combating Money Laundering Crimes and What are the Impacts of Money Laundering. This research is a normative legal research that is prescriptive and technical or applied. The research approach uses the law approach and case approach. The type of research data is secondary data with primary and secondary legal materials. Data collection techniques such as literature study and data analysis techniques used are deductive. The results of this study explain that the duties and authority of the Financial Transaction Reports and Analysis Center (PPATK), there are two (2) main tasks that stand out in relation to the prevention and eradication of money laundering, namely: detecting the occurrence of money laundering by looking at the report conducted by Reporting Parties, namely Providers of Financial Services (banks) concerning Suspicious Financial Transactions (TKM); and assist law enforcement relating to money laundering and the criminal offenses that give birth (predicate crimes), and that the impact of money laundering is very detrimental to the community, because money laundering activities enable drug traffickers and traffickers, smugglers and other criminals can expand its activities; money laundering will undermine the financial community because such a large amount of illicit money is involved and circulating and opportunities for corruption are wide open; also money laundering reduces government revenue from the tax sector.